A Perspective On COVID-19 Vaccine Hesitancy in India - Tanmaye Rameneni; Tooba Sayeed; Sumit Kumar (Medsci Publications, 2022)
India started vaccination drives in January of 2021. One of the biggest challenges faced by the government was the hesitancy to get vaccinated. Vaccine hesitancy causes the vaccination process to be delayed, affecting the process of building herd immunity and allowing the virus to evolve. Certain anthropological factors are responsible for vaccine hesitancy in a community. These factors are broadly categorised as personal beliefs, the role of media, and religion. An in-depth analysis of available literature, including the grey literature indicated that these factors influence an individual's decision-making. Vaccine hesitancy was largely affected by rumours surrounding it. Contradictory information regarding the vaccines created uncertainty about the consequences of getting vaccinated. A holistic approach is necessary to tackle vaccine hesitancy. The interventions from the government need to consider these social and cultural factors to address vaccine hesitancy in the future. Due to the diverse sample size, there is a need for various actors and stakeholders to come together and implement demographic-specific measures to address vaccine hesitancy in India.